Evaluation of Bacteriostatic Effect of Rosemary and Oregano Essential Oils Against a Non-Pathogenic Surrogate of Salmonella spp. (E. coli ATCC 9637) - Theodore John Magtalas; Gerieka Ramos Anapi (Biology and Life Sciences Forum, 2025)
Control of bacterial growth in food is essential to maintaining food quality and safety. The use of food additives is one answer raised to address this problem. However, some synthetic antimicrobial additives pose minor to serious health risks to consumers. Natural antimicrobial additives are potential alternatives to synthetic additives that can control microbial growth without significant health risks. This study evaluated the bacteriostatic effect of rosemary essential oil (REO) and oregano essential oil (OEO) against E. coli ATCC 9637, a non-pathogenic surrogate of Salmonella spp. in culture and in raw chicken breast. Final concentrations of 1.5% REO and 0.15% OEO were added to cultures of E. coli ATCC 9637, and the growth rate was evaluated. Raw chicken breast pieces were dipped in E. coli ATCC 9637 cultures prior to being dipped in 1.5% REO and 0.15% OEO. The chicken samples were then taken at two-day intervals, and the growth of E. coli ATCC 9637 was analyzed. No growth was observed in the cultures after a 24 h incubation period. The chicken samples treated with 1.5% REO resulted in a 0.69 log reduction compared to the positive control, while those treated with 0.15% OEO resulted in a 0.31 log reduction (p < 0.05). This shows that REO and OEO are effective against E. coli ATCC 9637 and have promise as natural antimicrobial agents.